PECULIARITIES OF ETHICS OF BUSINESS COMMUNICATION IN THE MODERN MARKET ENVIRONMENT - Boryshkevych, I.I (The actual problems of regional economy development, 2021)
The success of any organization directly depends on the effectiveness of business communication. In order for communication to be effective, it is necessary to follow the norms and rules of ethics. Ethics of business communication involves choosing an effective way to establish a relationship and exchange information between the organization and stakeholders, managers and employees, as well as within the organization. In addition, it regulates the job responsibilities of employees, their external and internal behavior, as well as builds the business reputation of each individual employee. Thanks to the norms, rules and principles of ethics, employees of the organization manage to maintain a friendly atmosphere in the team, avoid disputes and misunderstandings. The purpose of writing this article is to study the features of business ethics in today's market environment and find ways to improve it. The article describes the concepts of “communication” and “business communication”. The functions of business communication are described, among which the following were singled out: communication of job responsibilities to employees, providing feedback, interaction with stakeholders, motivation of employees and the formation of social ties. The relationship of the main elements of business communication is shown. Such elements include: sender of information, business information, channel and method of communication, recipient of information and feedback. Each element is integral and plays an important role in the implementation of the communication process. The characteristics of the components that should be considered in the organization in order to improve the ethics of business communication are given and implemented: transparency, emotional intelligence, non-verbal communication, clarity, listening and speed. There are communication barriers in business communication that can hinder its successful implementation. The main communication barriers are classified and grouped into three groups: external, organizational and personal. Rules have been proposed to ensure successful negotiations. The main objectives of the negotiations are to find a mutually beneficial solution and reach an agreement or an agreement.